Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

If SinA=2pq/p[square}+q[square] Pt SecA-Tan A=p-q/p+q

Asked by chethan U 22nd July 2012, 5:27 PM
Answered by Expert
Answer:
Answer : Given :SinA=2pq / (p2+q2)
To Prove : SecA - Tan A= (p - q ) / (p+q)
 
Now , 
=> SinA = 2pq / (p2+q2)
Using componendo and dividendo,we get 
=> ( sinA +1 ) / (sinA -1) = ( 2pq + p2 + q2 ) / (p2 + q2 - 2pq )
Inverting the values we get ,
 => ( sinA - 1 ) / (sinA + 1) =  (p2 + q2 - 2pq ) / ( 2pq + p2 + q2)
=> ( sinA - 1 ) / (sinA + 1) = (p - q)2 / ( p + q)2
rationalising LHS
=> (1- sinA)2 / ( 1- sin2A ) = (p - q)2 / ( p + q)2
=> (1- sinA)/ cos2A = (p - q)2 / ( p + q)2     { using sin2A + cos2A =1 ,
                                                                           => 1- sin2A = cos2A }
taking the squareroot both the sides , we get 
=> (1- sinA) / cosA = (p - q) / ( p + q)
=>(1/ cosA) - (sinA / cosA) = (p - q) / ( p + q ) 
=> secA - tanA = (p - q) / ( p + q)        { using secA = 1/cosA and                                                                           tanA = sinA/cosA }
Hence Proved 

Answered by Expert 22nd July 2012, 8:11 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Free related questions

Chat with us on WhatsApp